Surgical myocardial revascularization without extracorporeal circulation - Ordinola Rojas,Salomón Soriano (2003)
OBJECTIVE: To assess the immediate postoperative period of patients undergoing myocardial revascularization without extracorporeal circulation with different types of grafts. METHODS: One hundred and twelve patients, 89 (79.5%) of whom were males, were revascularized without extracorporeal circulation. Their ages ranged from 39 to 85 years. The criteria for indicating myocardial revascularization without extracorporeal circulation were as follows: revascularized coronary artery caliber > 1.5 mm, lack of intramyocardial trajectory on coronary angiography, noncalcified coronary arteries, and tolerance of the heart to the different rotation maneuvers. RESULTS: Myocardial revascularization without extracorporeal circulation was performed in 112 patients. Three were converted to extracorporeal circulation, which required a longer hospital stay but did not impact mortality. During the procedure, the following events were observed: atrial fibrillation in 10 patients, ventricular fibrillation in 4, total transient atrioventricular block in 2, ventricular extrasystoles in 58, use of a device to retrieve red blood cells in 53, blood transfusion in 8, and arterial hypotension in 89 patients. Coronary angiography was performed in 20 patients on the seventh postoperative day when the grafts were patent. CONCLUSION: Myocardial revascularization without extracorporeal circulation is a reproducible technique that is an alternative for treating ischemic heart disease.